A volumetric study of the choroid plexus in neuropsychiatric systemic lupus erythematosus - Hu Liu; Huiyang Liu; Huanhuan Li; Bailing Tian; Zhen Sun; Wen Xiong; Zhenxing Li; Pingting Yang; Guoguang Fan (Scientific Reports)
Abstract Much evidence suggests that the choroid plexus (CP) plays an important role in the pathophysiology of systemic lupus erythematosus (SLE), but its imaging profile in neuropsychiatric SLE (NPSLE) remains unexplored. To evaluate CP volume in NPSLE patients using MRI. This retrospective study evaluated patients with SLE who underwent MRI of the brain, including three-dimensional T1-weighted imaging. CP volumes were automatically segmented. CP volume was evaluated using multivariable linear regression adjusted for age, sex, and total intracranial volume among three groups: NPSLE group, non-NPSLE group, and healthy control group (HC). Correlation analysis was performed between CP volume and clinical variables in the patient group. A total of 138 patients with SLE were included in the analysis. It was found that the right CP volume was greater in NPSLE compared with non-NPSLE and HC. When stratified according to their diagnosed status, newly diagnosed NPSLE had significantly greater CP volumes bilaterally compared with HC. Right CP volume was positively associated with Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) scores in the patient group. All statistical significance levels were p < 0.05. CP enlargement could reflect a neuroinflammatory response that occurs at NPSLE disease onset. CP volume may serve as a promising marker for SLE, especially for newly diagnosed NPSLE.